Urgensi pengelolaan pariwisata Kampung Heritage Kajoetangan Malang - Moch. Nurfahrul Lukmanul Khakim; Maria Ulfa Utami Putri; Wikan Suktianto; Nur Andari Budi (Jurnal Teori dan Praksis Pembelajaran IPS, 2019)
Malang City as one of the cities of cultural tourism and history in East Java has its own charm, one of which is village tourism. Village tourism with the feel of thematic cultural entertainment named Heritage Kayutangan Village has not been well managed since it was founded a year ago. This research method is qualitative with observation and interviews. Kayutangan Malang Heritage Village has a unique appeal with the classic nuances of the past. Kampung Kayutangan offers several facilities such as village lines, old house visits, photo spots, traditional game spots, past photo galleries, antique galleries and ancient culinary variety. The potential of Heritage Kayutangan Village has not been managed properly. Two historical tourism management strategies offered are setting appropriate city government policies and effective promotions to increase tourism attractiveness.DOI: 10.17977/um022v4i12019p015